2018
DOI: 10.1021/acsaem.8b01385
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of PtCu Alloyed Nanocages with Highly Open Structures as Bifunctional Electrocatalysts for Oxygen Reduction and Polyhydric Alcohol Oxidation

Abstract: Three-dimensional (3D) bimetallic PtCu alloyed nanocages (NCs) with highly open structures and large external-and internal-surfaces accessible for reactants were facilely synthesized by a one-pot solvothermal method. Arginine and cetyltrimethylammonium chloride (CTAC) acted as the costructure-directors and stabilizing agents. The resultant PtCu NCs showed significantly enhanced catalytic activity and improved stability when compared to commercial Pt/C (50 wt %) and Pt black catalysts toward oxygen reduction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…The mass activity (MA) of O -PtCuNF/C (2.47 A mg Pt –1 ) was also 2.1 and 7.7 times higher than those of D -PtCuNF/C and Pt/C, respectively (Figure d). Importantly, the MA of O -PtCuNF/C surpasses those of PtCu-based ORR catalysts reported to date, including PtCu/Pt core/shell NPs, PtCu intermetallic NPs, and tailored PtCu nanoarchitectures (Figure e). , We note that O -PtCuNF/C w/o SiO 2 showed ECSA Hupd and ORR activity much lower than that of O -PtCuNF/C, highlighting the crucial role of silica coating (Figure S12).…”
mentioning
confidence: 79%
“…The mass activity (MA) of O -PtCuNF/C (2.47 A mg Pt –1 ) was also 2.1 and 7.7 times higher than those of D -PtCuNF/C and Pt/C, respectively (Figure d). Importantly, the MA of O -PtCuNF/C surpasses those of PtCu-based ORR catalysts reported to date, including PtCu/Pt core/shell NPs, PtCu intermetallic NPs, and tailored PtCu nanoarchitectures (Figure e). , We note that O -PtCuNF/C w/o SiO 2 showed ECSA Hupd and ORR activity much lower than that of O -PtCuNF/C, highlighting the crucial role of silica coating (Figure S12).…”
mentioning
confidence: 79%
“…Despite their successful etching treatment, structural collapse is inevitable to some extent in other samples. To solve this problem, Feng's group reported a facile one‐pot method for the fabrication of PtCu alloy nanocages with a well‐defined structure . They argued that arginine serves as the most important structure‐directing agent (Figure d).…”
Section: Three‐dimensional Nanostructuresmentioning
confidence: 99%
“…d) Schematic illustration of the PtCu nanocages (reprinted with permission from Ref. , Copyright 2018 American Chemical Society).…”
Section: Three‐dimensional Nanostructuresmentioning
confidence: 99%
“…Meanwhile, precisely controlled fabrication of Pt-based alloys with tailored facets and compositions can not only improve the utilization efficiency of Pt, but also modify the electronic and geometric structures, thus benefiting for achieving higher catalytic activities [40][41][42][43]. Recently, Feng and co-workers [44] demonstrated that bimetallic PtCu alloyed nanocages with high-index facets exhibited enhanced catalytic activities toward oxygen reduction and polyhydric alcohol oxidation. Remarkably, massive studies show that onedimensional (1D) nanowires (NWs) exhibit enhanced electrocatalytic activity owing to their large surface area, high surface electron conductivity, surface defects, and abundant unique quantum effects [45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%